Bile Acid Malabsorption in Chronic Diarrhea: Pathophysiology and Treatment - Alan Barkun; Jonathan Love; Michael Gould; Henryk Pluta; A Hillary Steinhart (Canadian Journal of Gastroenterology)
BACKGROUND: Bile acid malabsorption (BAM) is a common but frequently under-recognized cause of chronic diarrhea, with an estimated prevalence of 4% to 5%.